2009
DOI: 10.1136/jnnp.2009.174573
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment predicts poststroke death in long-term follow-up

Abstract: Background: Poststroke global cognitive decline and dementia have been related to poor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 59 publications
6
99
2
5
Order By: Relevance
“…2 One study found that poststroke CIND is a negative predictor of survival. 3 Studies have also shown that poststroke dementia (PSD) increases the risk of recurrent vascular events. 4,5 However, no studies to date have examined the effect of CIND on poststroke recurrent vascular events or dependency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 One study found that poststroke CIND is a negative predictor of survival. 3 Studies have also shown that poststroke dementia (PSD) increases the risk of recurrent vascular events. 4,5 However, no studies to date have examined the effect of CIND on poststroke recurrent vascular events or dependency.…”
mentioning
confidence: 99%
“…Previous studies that have examined the prognostic abilities of domain-specific impairments have found that visual memory impairments predict for disturbances in activities of daily living, 8 whereas executive functioning and visuospatial impairments 3,9 predict for poor survival after stroke. Therefore, in this study, we aimed to determine domain-specific predictors of dependency, recurrent vascular events, and death.…”
mentioning
confidence: 99%
“…1,2,12 Beyond, animals in our model exhibit deficits in memory, visuospatial abilities, and executive function, thus resembling the clinical features of multi-infarct dementia. 13 Another advantage of our model is the use of adult mice without comorbidities, which excludes confounding risk factors for vascular dementia and nonstroke-related cognitive impairment. A limitation of the presented model is that large sample sizes are needed to detect behavioral improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Prejuízo da FE após AVC tem sido descrito em 30% a 76% dos casos Gutierrez Perez, Savborg et al ;Sundar and Adwani ;Hoffmann, Schmitt et al 2009;Oksala, Jokinen et al 2009), e está associado a recuperação funcional (Barker-Collo, Feigin et al ;Paolucci, Antonucci et al 1996;Patel, Coshall et al 2002) e AVD. (Pohjasvaara, Erkinjuntti et al 1998;Zinn, Bosworth et al 2007 …”
Section: Função Executiva E Avcunclassified
“…Apenas estudos mais recentes focaram a associação da depressão pós AVC mais especificamente com a FE. Esses estudos demonstraram maior morbidade em pacientes com essa associação (Pohjasvaara, Leskela et al 2002;Oksala, Jokinen et al 2009;Melkas, Vataja et al 2010 HL= hiperlipidemia; EP= estatina prévia; EC= estatina corrente; T= tabagismo atual; HT= história de tabagismo; HDA= história de dependência ao álcool; AIT= ataque isquêmico transitório; E= enxaqueca; ACO= anticoncepcional; * = Prontuário do paciente não localizado. HL= hiperlipidemia; EP= estatina prévia; EC= estatina corrente; T= tabagismo atual; HT= história de tabagismo; HDA= história de dependência ao álcool; AIT= ataque isquêmico transitório; E= enxaqueca; ACO= anticoncepcional; * = Prontuário do paciente não localizado.…”
Section: Análise De Colinearidadeunclassified